2021
DOI: 10.1158/1078-0432.ccr-20-5026
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Clinical Responses to Targeted Therapies by Patient-Derived Organoids of Advanced Lung Adenocarcinoma

Abstract: We demonstrated that in vitro drug responses in patient-derived organoids (PDOs) are correlated to clinical responses to targeted therapies in individual patients with advanced lung adenocarcinoma and PDOs can be used to identify effective anti-cancer therapies for novel molecular targets. PDOs recapitulated progression-free survival and objective responses of NSCLC patients receiving clinically approved targeted agents. PDOs also predicted activity of therapeutic strategies under clinical investigation. YUO-0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 57 publications
1
76
0
Order By: Relevance
“…Third-generation TKI osimertinib has also demonstrated potent activity against uncommon EGFR mutations in NSCLC ( 11 ). With the development of techniques, the clinical response of targeted drugs is also being tested in patient-derived organoids (PDOs) ( 12 ). The promise of PDOs as a patient-proximate culture system has led to great progress, with an increasing number of models emerging recently.…”
Section: Discussionmentioning
confidence: 99%
“…Third-generation TKI osimertinib has also demonstrated potent activity against uncommon EGFR mutations in NSCLC ( 11 ). With the development of techniques, the clinical response of targeted drugs is also being tested in patient-derived organoids (PDOs) ( 12 ). The promise of PDOs as a patient-proximate culture system has led to great progress, with an increasing number of models emerging recently.…”
Section: Discussionmentioning
confidence: 99%
“…LCOs can be used for selecting personalized medicine and predicting the drug response of patients. Cho et al showed that LCOs can predict drug responses such as progression-free survival and objective response [ 39 ]. LCOs have the potential for high-throughput drug screening [ 10 , 11 , 12 ].…”
Section: Lung Cancer Organoidsmentioning
confidence: 99%
“…Interactions with mesenchymal cells affect the differentiation and stemness of BASCs and AT2 cells [ 12 , 20 , 21 , 42 ]. For example, BASCs differentiate into alveolar lineages when cultured with endothelial cells [ 21 ], and type II cells produce alveolar spheres when cultured with fibroblasts [ 39 ]. Co-culture of type II pneumocytes and fibroblasts revealed that Wnt signaling maintains AT2 stemness and prevents differentiation to AT1 cells [ 43 ] ( Table 3 ).…”
Section: Lung Cancer Organoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, lessons we are learning in the advanced setting may be useful for customizing the therapeutical approach according to the molecular background of the disease and its evolution over time. Although many open issues are still to be answered regarding the management of tumor heterogeneity/resistance and, in this sense, the potential room for treatment combinations at baseline or at progression [42], innovative diagnostic tools coming from the preclinical as patient-derived organoids (PDOs) may accelerate the identification and development of effective therapeutic strategies able to assist the clinical decision-making process [43]. In this light, the identification and validation of reliable predictive biomarkers represent a crucial gap to be fulfilled.…”
Section: Open Issues: Managing Progression Patient's Selection and Profiling Anticipationmentioning
confidence: 99%